2016
DOI: 10.1002/hep.28625
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness of ledipasvir/sofosbuvir in 4,365 treatment‐naive, genotype 1 hepatitis C‐infected patients

Abstract: Real-world effectiveness data are needed to inform hepatitis C virus (HCV) treatment decisions. The uptake of ledipasvir/sofosbuvir (LDV/SOF) regimens across health care settings has been rapid, but variations often occur in clinical practice. The aim of this study was to assess sustained virologic response (SVR) of LDV/SOF6ribavirin (RBV) in routine medical practice. This observational, intent-to-treat cohort was comprised of 4,365 genotype 1, treatment-naive, HCV-infected veterans treated with LDV/SOF6RBV. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
157
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(184 citation statements)
references
References 23 publications
22
157
5
Order By: Relevance
“…More recently, in an integrated analysis of all phase III LDV/SOF studies, African American race was associated with decreased SVR rates in those receiving 8-week regimens of LDV/SOF [11]. A VA real-world cohort that included HCV monoinfected and HIV/HCV coinfected patients showed similar results in African Americans [12]. In a HIV/HCV co-infection clinical trial, Naggie and colleagues found that, when compared to non-black patients, black patients had lower SVR12 rates, 90% vs 99% p<0.001, respectively, and higher relapse rates [5].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…More recently, in an integrated analysis of all phase III LDV/SOF studies, African American race was associated with decreased SVR rates in those receiving 8-week regimens of LDV/SOF [11]. A VA real-world cohort that included HCV monoinfected and HIV/HCV coinfected patients showed similar results in African Americans [12]. In a HIV/HCV co-infection clinical trial, Naggie and colleagues found that, when compared to non-black patients, black patients had lower SVR12 rates, 90% vs 99% p<0.001, respectively, and higher relapse rates [5].…”
Section: Discussionmentioning
confidence: 89%
“…In the DAA era, African American race has been associated with lower SVR rates including those receiving 8 week LDV/SOF regimens [11][12] and in one 12-week clinical trial of HIV/HCV coinfection, both in genotype 1 (GT1) infections [5]. In ION-4, a study of LDV/SOF in HIV/HCV coinfection, the overall SVR rate was 96% but was only 90% in AfricanAmericans, reflecting all 10 relapses in the study, eight of whom received efavirenz-containing regimens [5].…”
Section: Introductionmentioning
confidence: 99%
“…Safety and efficacy of SOF‐containing HCV regimens have been formally evaluated in over 10,000 patients in registration studies5, 6 and real‐world cohorts 7, 8, 9. Overall, the use of SOF appears safe with few significant toxicities reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since the release of the first generation DAA's in 2011 there has been an explosion in the number and combination of DAA's available. Clinical trials have consistently reported SVR 12 rates >95% for most patient populations, including those patients co-infected with HIV, which have been supported by recent real world data (12)(13)(14). Treatment guidelines maintained as a living document online by the collaboration of American Association for the Study of Liver Disease (AASLD) and the Infectious Diseases Society of America (IDSA) are rapidly changing, however all oral DAA therapy is now the standard of care for all patient populations (15).…”
mentioning
confidence: 61%